Effect of Polymer Coatings to Impeller and Casing on the Performance of Centrifugal Pumping System - Reddy, K S; Bhandarkar, D M; Varshney, A C; Gharde, K D (Journal of Agricultural Engineering, 2007)
A computerized pump testing set up was used to assess the performance of centrifugal pumping system (5hp) by giving different coatings to the impeller and pump casing. The metallic coatings selected were stainless steel, aluminum and zinc. The polymer coatings selected were CP MECATEC 53 BL, CP MECATEC 8, Rust-I-Sol. Before applying the coatings, the impellers were treated with sand blasting for achieving clear surface. The coating was applied to impeller vanes and hub. Coating the impeller and casing with CP MECATEC 53 BL resulted in maximum increase of 5 % in system efficiency, as compared to control without coating. The corresponding input power consumption was 4.15 kW. At duty point of the pump set, the increase in the systems efficiency was 3.8% with input power consumption of 3.8kW, as compared to other treatments.